Meningkatkan Kepercayaan Diri Siswa Laki-laki Untuk Menari pada Siswa Kelas IX SMPN 8 Tanjabtim dengan Menggunakan Model ARCS (Attention, Relevance, Convidence, Satisfaction) - Permatasari, Tika (Indo-MathEdu Intellectuals Journal, 2023)
This research is classroom action research with the aim of increasing male students' confidence in dancing in class IX students at SMPN 8 Tanjabtim. The learning model used is the ARCS model (Attention, Relevance, Confidence, Satisfaction). This learning model is a framework designed to increase student motivation and involvement in the learning process. After implementing it for 1 cycle for 4 meetings, it was found that the results of applying the ARCS model in Arts and Culture learning had brought significant positive changes in male students' self-confidence in expressing dance movements. The change in attitude from disbelief to confidence, as well as the increase in student involvement, indicates that this learning model has had a big impact in improving the quality of Arts and Culture learning for male students